Gambaran Kepatuhan Protokol Kesehatan Anak Usia Sekolah di TPQ Ar- Rasyid Desa Pagerjurang Boyolali - Siti Muyasaroh; Rahmawatie Ratna Budi Utami (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Covid 19 is a new type of disease that has never been previously identified in humans. The emergence of Covid 19 forced everyone to comply with health protocols. Health protocol is a public health effort that refers to many actions that need to be taken in the context of health protocols like waering mask, hand higyne and social distance. Adhering to health protocols could reducing the number of Covid 19. To found out the description of health protocol compliance in school-age children at TPQ Ar-Rasyid in Pagerjurang Village.Research. Those type of research is quantitative with research methods descriptive survey. The sampling technique in this study was a total sampling technique, the sample on that study was 42 students at TPQ Ar-Rasyid Pagerjurang. Data analysis on that research is univariate analysis. Complianced with health protocols for school-age children at TPQ Ar-Rasyid is in the obedient and non-compliant category. The description of complianced with health protocols in school-age children at TPQ Ar-Rasyid in Pagerjurang Village shows 35 respondents (83.3%).